ANALYSIS OF ISLAMIC ACCOUNTABILITY AND ISLAMIC GOVERNANCE IN ZAKAT INSTITUTION - Novendi Arkham Mubtadi (Faculty of Economics and Business, Hasanuddin University, 2019)
Islamic accounting considers that accountability is perceived as a unity that can not be separated from one another. It makes a big difference to the basic goals of conventional accounting. Performance measurement is needed to ensure the company's operations in achieving its goals with the result that the need for Islamic governance in zakat institutions which is a good way of strength to run the process of managing an organization. The purpose of this study is to explain about Islamic governance and accountability of Islam in zakat institutions in Indonesia. This research uses qualitative method or conceptual study with descriptive-comparative study-analytical approach. The guidelines used in this study refers to the sharia enterprise theory in the conception of Islamic accountability's understanding as well as the zakat core principles to examine about Islamic governance.Â The result of this research is the concept of Islamic accountability listed in sharia enterprise theory (hablumminallah, hablumminannas, and hablumminal'alam) can be seen from the presentation of financial statements in accordance with applicable accounting standards, the utilization of technology in financial reporting is by uploading financial statements on the regular website. While the concept of Islamic governance can be done by considering the number of supervisory commissions, the number of professionals in the supervisory commission, and the frequency of meetings with the supervisory commission. Recommendation for the next researcher is to conduct an empirical study on zakat institution related to Islamic accountability and Islamic governance.